Impasses e possibilidades da atuação dos profissionais das bibliotecas da Rede Municipal de Belo Horizonte - Elaine Maria da Cunha Morais (2009)
This research assessed the role of professionals working in libraries in Belo Horizontes public school system, and had the following objectives: to identify the professionals working in the school libraries pertaining to this citys public school system; to determine their function within the library; to verify their schooling level; to check the degree of the professionals involvement with the schools pedagogic projects; to identify the activities these professionals carry out; to verify if they are knowledgeable on the public policies pertaining to this teaching space; and to investigate the founding policies of the School Library Program in Belo Horizontes Public School System. The corpus of this research includes the professionals working in the libraries within the system, with a focus on the assistant librarians. The research is built upon an analysis that includes both quantitative and qualitative approaches which led, first of all, to an exploratory study that made use of a questionnaire directed at the professionals in 176 school libraries. Additionally, nine librarians were interviewed, each representing one of the districts in which the system is divided. Data analysis revealed important information about the school libraries, their holdings, the professionals working there, the unresolved matters, their strategies, their difficulties and contradictions, the relation with the school community, their incentives, their resources, etc. The results highlight the need to reformulate certain aspects of the Library Revitalization Project (Programa de Revitalização das Bibliotecas), as well as to reevaluate the library professionals working conditions and the teachers perceptions of this space in the students educational process.